Implementation and effectiveness of corporate-driven smallholder cocoa certification schemes in Indonesia - Janne Bemelmans; Miet Maertens (Agricultural and Food Economics)
Abstract Voluntary sustainability standards (VSS) are a popular instrument in corporate social responsibility strategies of food processing and distribution companies. Yet, concerns emerge about companies capitalizing on VSS as a reputation-building and product-differentiation tool without investing in strong sustainability commitments on the ground. This article explores how the heterogeneity in interventions across three corporate-driven Rainforest Alliance cocoa certification schemes in South Sulawesi, Indonesia, shapes farm-level socioeconomic impacts. We conceptualize the implementation of VSS interventions along three mechanisms—i.e., control, market-based incentives, and capacity-building interventions—and into measurable farm-level indicators. We use primary survey data from 458 smallholder producers and a propensity score matching approach to estimate farm-level effects of certification. Results reveal large differences in farm-level interventions across certification schemes and positive effects on farm production and producer income in those schemes with the strongest interventions. Results point to the complementarity of control, market-based incentives, and capacity-building interventions in delivering beneficial farm-level effects. We highlight the role of processing and distribution companies, as operators of certification schemes, in effectively implementing VSS to deliver improved sustainability outcomes. Improved monitoring and enforcement of VSS implementation is needed to improve accountability in the transition toward sustainable food systems.